Pengaruh Fermentasi dengan SBP (Saus Burger Pakan) terhadap Kecernaan Bahan Kering dan Bahan Organik Tumpi Jagung (Journal of Microbiology, Biotechnology and Conservation, 2025)
This study aimed to evaluate the digestibility of dry matter (DMD) and organic matter (OMD) of corn cob residue (tumpi jagung) fermented with SBP (Saus Burger Pakan). The research was conducted in July–August 2022. Sampling was carried out at PT. Santosa Utama Sari, Bolo District, Bima Regency, while the fermentation process was conducted at Bima Vocational School for 14 days. Digestibility tests were performed at the Animal Feed and Nutrition Science Laboratory, Faculty of Animal Science, University of Mataram. The experiment was arranged in a Completely Randomized Design (CRD) with five treatments and three replications: TF (without fermentation), T0 (0% SBP + 2.5% molasses + 100 ml distilled water), T1 (2% SBP + 2.5% molasses + 80 ml distilled water), T2 (4% SBP + 2.5% molasses + 60 ml distilled water), and T3 (6% SBP + 2.5% molasses + 40 ml distilled water). Fermentation lasted for 14 days, followed by observations on physical properties (color, mold, and pH). Data were analyzed using analysis of variance (ANOVA) and Duncan’s Multiple Range Test (DMRT). The results showed that SBP fermentation significantly improved both DMD and OMD (P < 0.05). The average DMD values were TF (68.26%), T0 (70.85%), T1 (73.74%), T2 (75.73%), and T3 (76.48%). Meanwhile, the average OMD values were TF (69.69%), T0 (72.23%), T1 (75.18%), T2 (77.15%), and T3 (78.29%). The best DMD value was obtained with T2 (4% SBP), while the highest OMD value was obtained with T3 (6% SBP).